2021
DOI: 10.1128/aac.01949-20
|View full text |Cite
|
Sign up to set email alerts
|

Continued Low Efficacy of Artemether-Lumefantrine in Angola in 2019

Abstract: Background: Biennial therapeutic efficacy monitoring is a crucial activity for ensuring efficacy of currently used artemisinin-based combination therapy in Angola. Methods: Children with acute uncomplicated P. falciparum infection in sentinel sites in Benguela, Zaire, and Lunda Sul Provinces were treated with artemether-lumefantrine (AL) or artesunate amodiaquine (ASAQ) and followed for 28 days to assess clinical and parasitological response. Molecular correction was performed using seven microsatellite marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 20 publications
5
32
2
Order By: Relevance
“…However, when accounting for a 95% confidence interval, the 86.0–95.9% PCR-corrected efficacy range of AL indicates that continued frequent efficacy monitoring of this drug is warranted in Mali. These findings are not unlike those from Uganda [ 35 ], Angola [ 36 ], and Burkina Faso [ 37 ], which have also shown AL not performing as well as other artemisinin-based combinations, such as ASAQ and DP. Similar to the AL day 28 uncorrected efficacy of 83.4% in this study, two other studies from Mali examining day 28 uncorrected efficacy reported results of 83.8% and 84.5% [ 33 , 34 ] and the study performed in Burkina Faso by Tinto & al, gave 58.4% for ASAQ and 46.1% for AL [ 32 ].…”
Section: Discussioncontrasting
confidence: 68%
“…However, when accounting for a 95% confidence interval, the 86.0–95.9% PCR-corrected efficacy range of AL indicates that continued frequent efficacy monitoring of this drug is warranted in Mali. These findings are not unlike those from Uganda [ 35 ], Angola [ 36 ], and Burkina Faso [ 37 ], which have also shown AL not performing as well as other artemisinin-based combinations, such as ASAQ and DP. Similar to the AL day 28 uncorrected efficacy of 83.4% in this study, two other studies from Mali examining day 28 uncorrected efficacy reported results of 83.8% and 84.5% [ 33 , 34 ] and the study performed in Burkina Faso by Tinto & al, gave 58.4% for ASAQ and 46.1% for AL [ 32 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Mutations in the pfmdr1 gene have been shown to play a signi cant role in parasites' tolerance to some antimalarials such as chloroquine, amodiaquine, artemisinin derivatives and lumefantrine; N86 wild type allele is implicated in decreased sensitivity to lumefantrine while the 86Y mutant allele, in combination with mutations in the pfcrt gene, is associated with decreased sensitivity to chloroquine and amodiaquine [33][34][35]. Pfmdr1 results in our study revealed a high prevalence of the N86 allele (NFD and NYD haplotypes), a nding seen recently in other countries throughout Southern and East Africa [7,36,37]. In six sites in Madagascar in 2006, the NFD and NYD haplotypes were observed in only 21.8% and 8.0% samples, respectively, although these frequencies increased to 30.0% and 14.6% just one year later [38].…”
Section: Discussionsupporting
confidence: 66%
“…For AL, however, no recent studies to evaluate therapeutic e cacy have been done in Madagascar. Evidence of reduced AL e cacy has been described in SSA [10][11][12]; given that it is the second-line antimalarial in Madagascar, and has at times been used as the rst-line treatment due to shortages of ASAQ, describing its e cacy in Madagascar is important.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained previously collected and publicly available microsatellite genotyping data from five studies with 13 trial sites 14 18 ( Table 1 ). Seven microsatellite loci were included: TA1, Poly-α, PfPK2, TA109, TA2490, C2M34, and C3M69.…”
Section: Methodsmentioning
confidence: 99%